The wine collections and exhibitions in Zielona Góra from 1922 to 1934 - Cincio, Arkadiusz (In Gremium. Studies in History, Culture and Politics, 2019)
The article presents the development of the collections and the exhibitions related to the viticulture in Zielona Góra. The first museum collections documenting the history of the winemaking in Zielona Góra and the region were created before the First World War. Their development was related to technological progress and a gradual decrease in crop area. These collections are systematically developed, mainly by the Museum of the Lubusz Region in Zielona Góra. The history of wine exhibitions dates back to 1922. That year the Heimatmuseum in Zielona Góra was established. In the 1960s and 1970s, the permanent winemaking presentation was the leading exhibition of the Museum of the Lubusz Region in Zielona Góra. Currently, the viticultural history of the region is presented in several museums and other facilities located in the Lubuskie Voivodeship. Their functioning is supported by self-government authorities. The revitalizing viticulture is one of the main tourist attractions of the region.